Information Literacy Instruction during COVID-19 - Eva, Nicole (Partnership, 2021)
The quick shift to online instruction taken by most post-secondary institutions in spring 2020 continued into fall 2020 and, in most cases, spring 2021. A survey was conducted to discover how this online shift might have affected the number of instruction requests academic librarians received compared to a typical year. Results were somewhat mixed, but overall, information literacy instruction requests seem to have decreased as a result of the pandemic.